2012
DOI: 10.1002/aur.1227
|View full text |Cite
|
Sign up to set email alerts
|

Male Gender Bias in Autism and Pediatric Autoimmunity

Abstract: Lay Abstract Males have a higher incidence of autism than females by approximately 4 to 1. Similarly, males have a higher incidence of some pediatric autoimmune diseases as compared to females. The basis for these disparities is largely unknown. In recent years there is growing evidence that immune and autoimmune dysregulation may be involved in autism. It is suggested here that the hormonal and immune processes that may contribute to a male preponderance in some pediatric autoimmune disorders may play a role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 102 publications
0
12
0
Order By: Relevance
“…These results highlight the heterogeneity of symptoms found in ASD and indicate that males are differentially vulnerable to various environmental insults occurring during pregnancy. The basis for this male bias is unknown with theories including the “extreme male brain”, hormonal differences, and genetic influences (for a review see 60 .…”
Section: Discussionmentioning
confidence: 99%
“…These results highlight the heterogeneity of symptoms found in ASD and indicate that males are differentially vulnerable to various environmental insults occurring during pregnancy. The basis for this male bias is unknown with theories including the “extreme male brain”, hormonal differences, and genetic influences (for a review see 60 .…”
Section: Discussionmentioning
confidence: 99%
“…Also, it has been reported that the sex hormone regulates the expression of FOXP1 (Takayama et al, 2014;Fröhlich et al, 2017), SHANK (Berkel et al, 2018), and RORA (Sarachana et al, 2011), which is essential for ASD, further confirming the potential role of the AR signaling pathway on ASD development. This can partly explain why the androgen can be related to male/female bias to ASD (Becker, 2012;Schaafsma and Pfaff, 2014;Mogi et al, 2015). This is the first time that the potential mechanism for PCOS-mediated ASD development has been discovered through AR-mediated ERβ suppression, providing a potential target for PCOS-mediated ASD through AR suppression Lee et al, 2017;Cherskov et al, 2018;Shay et al, 2018).…”
Section: Prenatal Dht Exposure-mediated Autism-like Behaviormentioning
confidence: 92%
“…Autoimmune diseases, such as systemic lupus erythematosus, Sjogren's syndrome, and rheumatoid arthritis, occur more frequently in women than in men [ 2 ]. However, certain types of autoimmune diseases, such as Goodpasture syndrome in which antibodies attack the basement membrane in lung and kidney cells, occur more commonly in men than in women [ 3 ]. In addition, there is growing evidence that sex hormones may be attributed to the sex-related differences in humoral and cellular responses as well as in infections and vaccinations [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%